Actividades recreativas para mejorar la motricidad en niños -as y jóvenes con síndrome de Down en el Instituto de Educación Especial Huaquillas periodo lectivo 2011-2012. - Ramírez del Rosario, Jonathan Alberto (2013)
The development of gross motor skills plays a decisive role in the evolutionary process of human beings. This can be accomplished many times, but highlighting the difference with humans affected by Down syndrome who suffer from disharmonic, slow and dissimulation product malfunctions suffering logically change the horizon development.